2006
DOI: 10.1007/bf03021827
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanesthesia and Intensive Care Isoflurane tolerance against focal cerebral ischemia is attenuated by adenosine A1 receptor antagonists

Abstract: Purpose:To investigate the role of the adenosine A 1 receptor in the rapid tolerance to cerebral ischemia induced by isoflurane preconditioning. Methods: Seventy-five rats were randomly assigned into five groups (n = 15 each): Control, 8-cyclopentyl-1,3-dipropulxanthine (DPCPX), Isoflurane, DPCPX+Isoflurane and Vehicle+Isoflurane groups. All animals underwent right middle cerebral artery occlusion (MCAO) for two hours. Isoflurane preconditioning was conducted one hour before MCAO in Isoflurane, DPCPX+Isofluran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 36 publications
1
25
0
1
Order By: Relevance
“…Another form of ischemic preconditioning in the brain can be elicited by volatile anesthetics (Kapinya et al, 2002;Zhao and Zuo, 2004;Bickler et al, 2005;Gray et al, 2005), which requires the activation of A 1 receptors (Liu et al, 2006) and p38 MAPK (Zheng and Zuo, 2004). In the present study, we showed that the inhibitory actions of adenosine A 1 receptors, but not other inhibitory receptors such as GABA B receptors, were attenuated by p38 MAPK inhibitors.…”
Section: Discussionsupporting
confidence: 52%
“…Another form of ischemic preconditioning in the brain can be elicited by volatile anesthetics (Kapinya et al, 2002;Zhao and Zuo, 2004;Bickler et al, 2005;Gray et al, 2005), which requires the activation of A 1 receptors (Liu et al, 2006) and p38 MAPK (Zheng and Zuo, 2004). In the present study, we showed that the inhibitory actions of adenosine A 1 receptors, but not other inhibitory receptors such as GABA B receptors, were attenuated by p38 MAPK inhibitors.…”
Section: Discussionsupporting
confidence: 52%
“…Some unspecific and specific adenosine A1 receptor antagonists abolished the ischemic tolerance. Moreover, Liu et al also demonstrated that isoflurane-induced tolerance against focal cerebral ischemia in the rat middle cerebral artery occlusion (MCAO) model was attenuated by adenosine A1 receptor antagonists [23] .…”
Section: Excitatory/inhibitory Neurotransmitters and Neuroprotectionmentioning
confidence: 99%
“…1-3). Because a large literature has shown previously that adenosine plays a central role in preconditioning (Nakamura et al, 2002;Liu et al, 2006b) and our in vitro analysis indicated that preconditioning was associated with a Cx43-dependent increase in adenosine (Fig. 6), we next tested the effect of the blood-brain barrier (BBB)-permeable adenosine A 1 receptor antagonist DPCPX during preconditioning.…”
Section: Cx43mentioning
confidence: 99%